2017
DOI: 10.12659/msmbr.902285
|View full text |Cite
|
Sign up to set email alerts
|

M3 Macrophages Stop Division of Tumor Cells In Vitro and Extend Survival of Mice with Ehrlich Ascites Carcinoma

Abstract: BackgroundM1 macrophages target tumor cells. However, many tumors produce anti-inflammatory cytokines, which reprogram the anti-tumor M1 macrophages into the pro-tumor M2 macrophages. We have hypothesized that the problem of pro-tumor macrophage reprogramming could be solved by using a special M3 switch phenotype. The M3 macrophages, in contrast to the M1 macrophages, should respond to anti-inflammatory cytokines by increasing production of pro-inflammatory cytokines to retain its anti-tumor properties. Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…M2 can be further divided into four subsets, namely M2a, M2b, M2c, and M2d, under different stimuli (Murray et al, 2014). TGF stimulates macrophages to differentiate into M3, which has the ability to suppress tumor growth (Kalish et al, 2017). CXCL4, a platelet-derived chemokine, is a potent stimulus that promotes macrophage polarization into the M4 phenotype, which has reduced phagocytosis and significantly downregulates CD163 expression (Gleissner et al, 2010).…”
Section: Plasticity Of Macrophagesmentioning
confidence: 99%
“…M2 can be further divided into four subsets, namely M2a, M2b, M2c, and M2d, under different stimuli (Murray et al, 2014). TGF stimulates macrophages to differentiate into M3, which has the ability to suppress tumor growth (Kalish et al, 2017). CXCL4, a platelet-derived chemokine, is a potent stimulus that promotes macrophage polarization into the M4 phenotype, which has reduced phagocytosis and significantly downregulates CD163 expression (Gleissner et al, 2010).…”
Section: Plasticity Of Macrophagesmentioning
confidence: 99%
“…[50][51][52] Macrophages are capable of differentiating into six additional subpopulations: regulatory (Mreg), hematophage-associated (Mha), oxidative (Mox), M3, M4, and M17 macrophages ( Table 1). [53][54][55][56] Mreg macrophages respond to the stimulation of Treg cells and are responsible for inducing the repair response and inhibiting triggering of mechanisms that produce pro-inflammatory cytokines in tissue lesions. [57][58][59] Mox macrophages differ from the other cell types in expressing oxidized 1palmitoyl-2-arachidonoyl-sn-glycero-3-phosphorylcholine and producing HO-1 and sulfiredoxin-1.…”
Section: Macrophage Phenotypesmentioning
confidence: 99%
“…This observation, support the hypothesis about the transition of M1 cells to M3 cells during tumor proliferation ( 78 ). Kalish et al reported that the M3 phenotype exhibited an antiproliferative antitumor effect in vitro , and prolonged the survival time of mice with Ehrlich ascites carcinoma ( 79 ). Nevertheless, more studies are needed to fully characterize and understand the activity of the M3 macrophages.…”
Section: Breast Cancer As An Inflammatory Processmentioning
confidence: 99%